Analysis of Village Fund Allocation Management in Yoka Village, Heram District, Jayapura City, Papua Province - Vince Tebay (Formosa Journal of Applied Sciences, 2023)
This study aims to analyze the implementation of the Village Fund Allocation in Yoka Village since it was rolled out in 2016. The method used is qualitative and literature study. Data comes from interviews, observations, documentation, and literature sources that are relevant to the topic of study. Data analysis was carried out through the stages of presenting data, data reduction, and drawing final conclusions. The results of this study indicate that the Village Fund Allocation management cycle includes Planning, Implementation, Administration, Reporting and Accountability. The management of Village Fund Allocation carried out by the Yoka Village Government has followed the technical guideline rules that have been regulated in laws and regulations, but the process is still not optimal. This can be seen from the process of reporting and accountability which experienced delays.